PAUD As an Investment for Personal Children, Families and Communities: A Review of the Economics of Unesco and Islam - Maryam Batubara (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PAUD is an institution that has a mission to grow, teach, foster and develop potential and talents according to their development. This research belongs to or uses a descriptive qualitative approach. Data collection was carried out by reading 28 reference books and reading sources related to the object of research. The research results show that UNESCO is important in organizing PAUD. PAUD itself is a very profitable form of investment for families, communities and children. Judging from its advantages that PAUD can help get the right stimulation for growth and development and influence the success of children in the future, for families investing in PAUD will be able to shape the personality of children who are quality and able to compete at the local, regional and global levels. Likewise with the community, through investment at the PAUD level children will be trained and fostered on how to interact, ethics, morals, and rules that exist in society. Thus later the child can carry out his role as part of society.